Service and network cross-layer resource allocation - Tan, Chong You. (2010)
Destination-Sequenced Distance-Vector (DSDV) is an ad-hoc network that cooperative engages a collection of mobile nodes without any deployed/existing communication infrastructure. Packets are transmitted between the mobile nodes of the network along a known route from the forwarding/routing table stored at each node. Therefore to maintain the consistency of the routing tables in a dynamically varying topology, each node periodically advertises updates of new/broken route to its current neighbor. So to effectively select a better route among all the updates, we propose route utilization metric, where apart from the convention of only choosing the least hops, we also take into consideration the interface queue (ifq) of the mobile node as part of the route selection criterion, in an attempt to divert from the route with congestion of packets at ifq along the mobile nodes. Three ad-hoc network protocols U-DSDV (modified DSDV to include route utilization metric), DSDV and DSR are simulated using Network Simulator 2 (NS-2) package and are compared in terms of total packet drop, routing packet drop and ifq packet drop in three different scenarios; each having varying number of maximum connections. We argue that the lack in improvement for the simulation results of U-DSDV as compared to DSDV is due to the fact that most of the dropped packets occur at the routing layer, not ifq, and hence, the route utilization metric is not leveraged. Whereas for DSR, we show that most of the dropped packets occur at ifq, as a result, the route utilization metric might be better suited for DSR.